MyBuku Pink mobile application using Android / NorHafizah Ayob, Mohammad Hafiz Ismail and Tajul Rosli Razak - Ayob, NorHafizah; Ismail, Mohammad Hafiz; Razak, Tajul Rosli (College of Computing, Informatics and Media, UiTM Perlis, 2023)
MyBuku Pink mobile application is based on the Pregnancy Check-up Book (Buku Pink) administered by the Malaysian Health Government, which permits periodic health checks after a user's pregnancy has been verified. (Rosely & Jawawi, 2021) stated that once a woman becomes pregnant in Malaysia, she must register for her pregnancy Buku Pink at government clinics or the Klinik Kesihatan Ibu dan Anak. According to the study, people in Malaysia have expressed dissatisfaction with the time it takes to sign up for the pregnancy book at government clinics. A checkup for pregnancy at a government clinic usually takes between one and three hours. The use of manual Buku Pink does not provide advanced features likes notifications, and pregnant women tend to forget their appointment. Also, in government clinics, antenatal and postnatal patient appointments are still handled using hardcopies and paper, resulting in high paper consumption. This project uses an agile model for this project as it is most suitable and provides a complete guideline to develop this mobile application successfully. Future work on this project can be applied by making MyBuku Pink in an Ios environment so that this application can use by both users of operating systems.